Financial Literacy, Investment, and Digital Financial Information Training at SMAS Garuda Palangka Raya - Made Ayu Artharini Koesanto, Stefani; Husnatarina, Fitria; Rahmaddian; Yovita; Rubyasih, Arina; Windyaningrum, Rachmawati (Unram Journal of Community Service, 2025)
Financial Literacy, Investment, and Digital Financial Information Training at SMAS Garuda Palangka Raya. Increasingly complex economic dynamics encourage people to look for additional sources of income outside their main job. Investment has emerged as a popular alternative. However, being successful in investing is highly dependent on an individual's level of financial literacy, investment experience, and risk profile. This community service aims to increase public awareness, especially among students and teachers at SMAS Garuda Palangka Raya, who often use online shopping applications and pay-later payment schemes. The digital transactions habits among students and teachers that are not balanced with basic knowledge about financial management and investment can trigger excessive consumer behavior. With 31 participants from SMAS Garuda Palangka Raya, the team successfully trained and gave information about how to budget, manage income and also invest using a fintech application. The training evaluation concluded that participants had improved their understanding of financial management and investment. The majority of participants also understand the function of an emergency fund and have a sense of how to deal with investments with irrational levels of profit and how to deal with debt. By implementing financial management, investment, and digital financial information literacy training, the training participant will be able to develop more responsible financial behavior and avoid debt traps, and also in order to prevent high-risk financial practices, such as dependence on high-interest loans to meet consumer needs.